Three essays in finance - Qian, Shuoge (Nanyang Technological University, 2024)
My thesis contains three essays in finance field, including corporate productivity, government intervention and marketisation, behavioural asset pricing with affect heuristic, gambling and overconfidence, index reconstitutions, index tracking funds, arbitrageurs, and security lending. In Chapter 1, in light of the rising global interest in state interventions, we examine the efficacy of the Chinese government's infrastructure investment in enhancing firm productivity. Using a policy shift requiring regional governments to bolster private firm protections, we find that infrastructure investment is particularly effective in improving firm productivity in regions with enhanced protections for private firms. We also show that the infrastructure investment implemented as part of China’s 2008 stimulus program was more effective in regions characterized by a conducive business environment for firms. Our analysis underscores the complementarity between state interventions and the development of market mechanisms. In Chapter 2, we present a multi-asset model where investors with gambling propensities trade with overconfident investors and investors susceptible to an affect heuristic. Gamblers derive extra utility from their stock positions, overconfident investors overestimate the precision of their information, and affect investors’ attitude towards a firm’s products impacts their investment in the firm’s stock. Our analysis indicates that gambling amplifies trading volume and mitigates excess return co-movement caused by overconfidence. Further, risk-adjusted returns decrease in the strength of the affect heuristic, but this negative relationship attenuates when the gambling propensity is high. Empirical evidence supports these implications. In Chapter 3, using the reconstitution of MSCI indices in seven Asian markets from 2006 to 2021, we discover arbitrage opportunities arising from index-tracking funds’ efforts to minimize tracking errors around the dates when index reconstitution changes become effective (i.e., effective dates). We document pronounced abnormal returns and trading volume on the last trading day before the effective date. Arbitrageurs can exploit this predictable pattern of stock price changes and earn sizable abnormal returns if they long the added and short the deleted stocks on the announcement date and close their positions at the end of the day before the effective date. Additional analysis reveals how index-tracking investors and arbitragers trade against each other to shape stock prices and equity-lending activities around MSCI index reconstitutions